A 28 GHz 2 × 2 Antenna Array with 10 Beams Using Passive SPDT Switch Beamforming Network - Firas Abdul Ghani (MDPI AG, 2021)
In this paper, a dual-polarized four-port 2 × 2 series fed antenna array operating at 28 GHz with beam-switching capability is proposed. The antenna array uses a simple passive beamforming network to switch the main beam. The presented antenna design is suitable for 5G user equipment and high data rates applications by which it has a compact size with low cost and complexity. The size of the antenna is 37.2 × 37.2 mm<semantics>2</semantics> including the ground plane, and it produces 10 different switched beams by using only two simple 3 dB/90<semantics>∘</semantics> couplers which create the required amplitudes and phase excitations for the antenna elements. A one-port simple feeding mechanism including Peregrine PE42525 SPDT switch modules and a power divider is used to generate and measure the 10 switched beams. The antenna design is implemented on a two-layer 0.203 mm thick low-loss (<semantics>tanδ</semantics> = 0.0027) Rogers 4003C substrate, and it has a measured 10 dB impedance bandwidth of 4 GHz (14.3%, from 26 GHz to 30 GHz) for all ports. Measured peak isolation between any dual-polarized ports of the antenna is better than 30 dB. The antenna has an average measured realized gain of 8.9 dBi and around 10 dB side lobe level (SLL) for all beams. The antenna has 3-dB coverage of 80<semantics>∘</semantics> to 90<semantics>∘</semantics> in 2D space and it has a maximum of ±26<semantics>∘</semantics> beam-steering angle. The antenna is designed and simulated using Ansys HFSS and fabricated using regular PCB processing.